Formulation and Evaluation of Controlled Release Microspheres of Acyclovir for Antiviral Therapy (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: Controlled drug delivery system (CDDS) provides the continuous oral drug delivery at predictable andreproducible kinetics for a predetermined period throughout the course of Gastro intestinal transit and emergesvarious routes of administration to achieve oral controlled drug delivery. Aim of this study was to formulate andevaluate controlled release microspheres of Antiviral drug, Acyclovir. Polymethacrylates (Eudragits) used as releaseretardant polymer material. Material & Methods: Microspheres prepared by non-aqueous solvent evaporationmethod using alcohol/light liquid paraffin. Magnesium stearate act as a droplet stabilizer and n-hexane is to hardenthe microspheres. The microspheres evaluated for their compatibility study Fourier transform infra-red(FT-IR),differential scanning calorimeter(DSC), flow & micromeritics properties, particle size, drug content, entrapmentefficiency, In vitro dissolution study in both 1.2 and 6.8 pH buffer, Scanning Electron Microscope(SEM) andaccelerated stability study. Results & Discussion: The prepared microspheres were free flowing and sphericalshape. The actual drug content in microspheres showed entrapment and release controlled till 12h the rate of drugrelease was found to decrease with increasing sphere size. The compatibility studies showed no interactions informulations. Scanning electron microscope study of microspheres were Spherical and porous in nature. The bestfit release kinetics achieved was Hixon-crowell plot. Conclusion: The formulation and evaluation of ControlledRelease Acyclovir microspheres is influenced by drug to polymer ratio and particle size and was found to bedissolution controlled. The formulation enhanced bioavailability upto 24hrs.